TOLERANSI ANTAR UMAT BERAGAMA DI MALUKU SEBUAH PERTIMBANGAN FILOSOFIS - Fatlolon, Costantinus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2013)
Tolerance is an essential quality of maturity in religious life. This paper argues that tolerance presupposes mutual recognition and understanding among religious communities and the acceptance of different beliefs and practices. Tolerance as a peaceful coexistence can be realized as long as different religious traditions recognize the truth-claims of each person based on his or her religion or belief, and neutrality of the state through the constitution and regulations for all religions, especially minorities. Moreover, tolerance requires a healthy dialogue between civil and religious institutions for the sake of the human person and social harmony